EFEKTIVITAS MODEL PEMBELAJARAN KOOPERATIF TIPE NUMBERED HEADS TOGETHER DITINJAU DARI AKTIVITAS DAN HASIL BELAJAR MATEMATIKA - ., Komarudin (JURNAL E-DUMATH, 2016)
The aim of this research is to find out the effectiveness of cooperative learning modelNumbered Heads Together (NHT) type observed by activity and math learning result.This research is experimental research using Posttest-Only Control Design. Thepopulations was all of the students in first grade of the SMA Tri Sukses Natar. Thesamples of the research were taken by using the cluster random technique. Dataobtained based on the observation of the learning process and student achievement test.Each of these data are used to obatain studentsâ learning activities and results ofstudentsâ mathematics learning. The data analysis technique is done by usingproportion test. Based on the results of data analysis showed that the percentage ofstudents activity more than 70% and the perecentage of studentsâ mathematics learningoutcomes gained more than 65%. Therefore, the NHT learning model is said to beeffectively applied in the first grade of the SMA Tri Sukses Natar.Keywords: cooperative learning model NHT; learning activities; learning outcomes